Necesidad de realizar una reforma legal al código orgánico integral penal, en cuanto a establecer una adecuada penalización del delito de abuso de confianza - Armijos Narváez, José Eduardo (2017)
Our Constitution of the Republic in item 26 respectively Art.66 mention the right to property, as follows: "The right to property in all its forms, function and social and environmental responsibility. The right of access to the property will be effective with the adoption of public policies, among other measures. " This constitutional treatment of the property does not have a single point of order, but it can be deduced that the doctrine presents the Constitution of the Republic in respect of this right. Therefore, our Constitution conceives of the property as a "civil right", from the level of the individual, and as a means to achieve full moral and material development of the person. Thus being this body of law, states in Article 75 paragraph 6 that "The law shall establish due proportionality between offenses and criminal, administrative or other sanctions. That is, the legal security of the person is guaranteed in the event of violations that arise, by setting out a proportionality between the punishment and the damage. The breach of trust offense consists of the provision making the asset for himself or for another, one another's cabinet, the same that has been passed tenure and not the domain to the detriment of the taxpayer. However, the scope of the word transmission implies a transfer of rights, which means that the transfer of ownership to illicit breach of trust as budget is concerned, the material thing and physically be moved under any title permitted by law. Moreover, the Code of Criminal Integral in its Art.187 states: that; "The person who has, for himself or a third, of money, goods or property assets given on the condition return them or use them in a certain way, it shall be punished with imprisonment of one to three years. The same penalty is imposed on a person who, abusing the name of another, in blank document, extended her one document to the detriment of the party or of a third. " In law, the breach of trust is a crime where the offender abused the trust of the victim. One of the most common abuses of trust is the misappropriation of property, taking advantage of the victim granted the use or possession of such property The legal problem lies in the second paragraph of this article, since unlike the first paragraph, abuse of company is determined in a blank document of a person for a third, as are various events and should not be sanctioned Likewise, since the latter act has and brings more serious consequences, which fall in the property rights of the victim or abused. Hence the urgent need for a study and research on this issue, in order to determine the immediate to Art.187 of the Code of Criminal Integral legal reform regarding the breach of trust.